Hi there!
Your equation states 2(w + 7) + 6(3w - 1)
If parentheses touch a number like 2 and 6 in your case, you would have to multiply that number with what's in the parentheses.
Let's start 2(w + 7)
2 × w = 2w
2 × 7 = 14
Combine the answers and the equation.
2w + 14 + 6(3w - 1)
Lets do the same thing with the other part.
6(3w - 1)
6 × 3w = 18w
6 × (-1) = -6
Combine the answers and the equation again.
2w + 14 + 18w - 6
Subtract 14 from both sides.
2w + 14 + 18w - 6
-14 -14
You would end up with 2w + 18w -20
Add 2w and 18w. You could only add them because they are like terms.
2w + 18w = 20w
Combine the answer with the equation
20w - 20
Divide 20w on both sides.
20w ÷ 20w = 1
20w ÷ 20 = w
Your answer is w = 1
I hope this helped!~